An Analysis on Chinua Achebe’S Anthills of the Savannah: the Idea of Politics, Power and Betrayal: Exploring the Significance of Names in Chinua Achebe’s Anthills of the Savannah (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper examines the formation patterns and functions of names inChinua Achebe’s Anthills of theSavannah, motivated by the scanty scholarly studies on names in thetext. All the personal names in the text are studied and analyzed, usinginsights from contextual models. The paper identifies four types of names in Anthills: official names, firstnames, nicknames and institutional/titular names. It also picks out threedimensions of these names: branching, non-branching and active-mentioned, whichare associated with the types. It shows that the names have structural andformation patterns such as + title prefixing, +first name, +surname, indigenouslanguage form, coinage, abbronymy,clipping, qualification and full form representation. It also demonstrates thatthe names play contextual and ideological roles such as being interactionaltools, address terms, weapons of criticisms and vision projectors. The paperconcludes that names in Anthills are carefully chosen to serve particularthematic and stylistic purposes.